Unveiling the nursing self, a global response - Cervera Vallejos, Mirtha Flor (2024)
Being a nurse is embracing a vocation that transcends the profession; mediated by a deep commitment to human vulnerability. This involves not only the ability to alleviate the suffering of the sick person, but also the dedication to protecting their dignity and recognizing their intrinsic value as a human being. It is a call to be a beacon of hope in the darkest moments, where every gesture and every word can make a difference in the lives of those who trust nurses. They reason that the sick person needs them, perceiving how they rethink life and fear death or loneliness.